The Effect of Storage Time and Temperature of Pagoda Mustard Meatballs and Milkfish Fortification Based on Microbiological Quality - Netty Maria Naibaho; Rudito; Elisa Ginsel Popang; Mujibu Rahman (Formosa Journal of Applied Sciences, 2023)
Testing for salmonella sp. using Salmonella Shigella Agar (SSA) selective media with the Total Plate Count (TPC) method. The lowest ALT results for meatballs stored in the freezer at 0oC were 2.4 x10-5 colonies/ml and the total coliform shelf life was 30 days, which was less than 2400 APM/g, the sample met the standards set by BPOM in 2019, namely a maximum of 10-5 colonies/ml. While the results of the analysis of salmonella sp. the refrigerator and freezer methods with a shelf life of 30 days showed negative results, but the 4oC chiller storage and the other two methods showed positive results for the salmonella sp tested. Therefore, while making Pagoda mustard meatballs, milkfish substitutes can only be kept in a 4°C refrigerator for a maximum of 30 days (1 month).